(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to describe the quality of outpatient services atAnggeraja District Health Center, Enrekang Regency. This study used quantitative research. The sample was 78 people who were selected accidentally sampling. The research data were collected through observation, questionnaires and documentation. The data were analyzed using quantitative descriptive with the table method frequency. Data analysis was performed in the form of tables, pictures, frequency for testing the hypothesis. The results of this study indicated that the quality of outpatient services at the Puskesmas Anggeraja District as seen from dimensions of service quality, namely the tangible dimension (physical evidence), the dimension of reliability, dimension of responsiveness, dimension of assurance (assurance) and the empathy dimension (empathy). Services provided by the District Puskesmas Anggeraja was qualified because it had received good ratings by community based on the assessment indicators used, this was indicated by recapitulation of the five dimensions of service quality was in the range of interpretation 2.51-3.25. This showed that the quality of outpatient services provided in good quality. Keywords: quality of Puskesmas Services.